Imperial Questions and Social Identities - Lauren Banko (Revue des Mondes Musulmans et de la Méditerranée)
During the interwar period in the Middle East, and specifically in Palestine, the British and French introduced legal statuses and new notions of belonging in the form of nationality, citizenship and passport regulations. These new statuses for the former Ottoman subjects, the majority of whom were Arab, reflected colonial and imperial norms and they incorporated the changing international terminology of identity issued from the League of Nations and post-World War I treaties. The article analyses how the development of new social and political understandings of identity was shaped by both the British legislators and the Arabic-speaking national leadership in Palestine. It demonstrates how local, regional and international actors stopped framing Palestinian nationality as part of wider Ottoman and British imperial questions and arrived instead at varied understandings of this status as a national question. The Ottoman and British contexts both stimulated this new understanding of identity through reactions both against and in favor of provisions implicit in imperial notions of identity and belonging.Dans le Moyen-Orient et en particulier dans la Palestine de l’Entre-Deux-Guerres, les autorités françaises et britanniques ont introduit des statuts juridiques et de nouvelles notions de l’appartenance que ce soit la nationalité, la citoyenneté ou une réglementation des passeports. Ces concepts, nouveaux pour d’anciens sujets ottomans, en majorité arabes, reflétaient des normes coloniales et impériales ; ils prenaient en compte une transformation profonde des manières de définir les identités au sein de la Société des Nations et dans les traités diplomatiques signés après la Première guerre mondiale. Le présent article examine la manière dont de nouvelles appréhensions sociale et politique de l’identité furent à la fois forgées par les législateurs britanniques et des dirigeants arabophones en Palestine. Il démontre comment des acteurs locaux, régionaux et internationaux ont arrêté de concevoir la nationalité palestinienne comme une des composantes de plus larges ensembles impériaux ottoman et britannique et comment, selon diverses voies, ils en sont venus à envisager ce statut comme une question nationale.